Peptide Nucleic Acid Knockdown and Intra-host Cell Complementation of Ehrlichia Type IV Secretion System Effector - Sharma, Pratibha; Teymournejad, Omid; Rikihisa, Yasuko (Frontiers in Cellular and Infection Microbiology, 2017)
Survival of Ehrlichia chaffeensis depends on obligatory intracellular infection. One of the barriers to E. chaffeensis research progress has been the inability, using conventional techniques, to generate knock-out mutants for genes essential for intracellular infection. This study examined the use of Peptide Nucleic Acids (PNAs) technology to interrupt type IV secretion system (T4SS) effector protein expression in E. chaffeensis followed by intracellular complementation of the effector to determine its requirement for infection. Successful E. chaffeensis infection depends on the E. chaffeensis-specific T4SS protein effector, ehrlichial translocated factor-1 (Etf-1), which induces Rab5-regulated autophagy to provide host cytosolic nutrients required for E. chaffeensis proliferation. Etf-1 is also imported by host cell mitochondria where it inhibits host cell apoptosis to prolong its infection. We designed a PNA specific to Etf-1 and showed that the PNA bound to the target region of single-stranded Etf-1 RNA using a competitive binding assay. Electroporation of E. chaffeensis with this PNA significantly reduced Etf-1 mRNA and protein, and the bacteria’s ability to induce host cell autophagy and infect host cells. Etf-1 PNA-mediated inhibition of ehrlichial Etf-1 expression and E. chaffeensis infection could be intracellularly trans-complemented by ectopic expression of Etf-1-GFP in host cells. These data affirmed the critical role of bacterial T4SS effector in host cell autophagy and E. chaffeensis infection, and demonstrated the use of PNA to analyze the gene functions of obligate intracellular bacteria.